2012
DOI: 10.1210/jc.2012-2410
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Signaling Axis HIF-1α/MicroRNA-210/ISCU Independent of SDH Mutation That Defines a Subgroup of Head and Neck Paragangliomas

Abstract: Collectively, this study unveiled a putative signaling axis of HIF-1α/miRNA-210/ISCU in a subset of HNPGLs that could have an impact on SDHB protein stability by a mechanism independent of SDH mutations, thus providing a foundation to better understand the functional interplay between HIF, miR-210, and mitochondria and its relevance in the pathogenesis of HNPGLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 22 publications
5
57
1
Order By: Relevance
“…Although glycolysis is not as efficient for ATP generation, it is the fastest method of ATP production and requires the least energy for cell survival under oxidative stress conditions. Recent studies have revealed that the energy metabolism shift regulated by the miR-210-ISCU pathway is involved in many hypoxia-related physiologic and pathologic processes [45-47]. In our study, the downregulation of ISCU mRNA and protein levels after miR-210 transduction further supports the idea that ISCU is regulated by miR-210.…”
Section: Discussionsupporting
confidence: 85%
“…Although glycolysis is not as efficient for ATP generation, it is the fastest method of ATP production and requires the least energy for cell survival under oxidative stress conditions. Recent studies have revealed that the energy metabolism shift regulated by the miR-210-ISCU pathway is involved in many hypoxia-related physiologic and pathologic processes [45-47]. In our study, the downregulation of ISCU mRNA and protein levels after miR-210 transduction further supports the idea that ISCU is regulated by miR-210.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the NF1 and RET-mutated PC/PGLs in this study had miR-210 levels not different from normal adrenal medulla tissue, again consistent with the distinct, non-hypoxic gene expression signature previously described in these tumours (Dahia & Familial Pheochromocytoma 2006). Interestingly, a previous report showed miR-210 overexpression in parasympathetic PGL of the head and neck (HNPGLs) which was independent of germline SDH mutations (Merlo et al 2012), a finding which is consistent with more universal association of HNPGLs with hypoxic gene expression regardless of whether SDH deficiency is present or not. Our study did not include HNPGLs, and we cannot therefore state whether miR-210 is different in PGL arising from chief cells (HNPGLs) compared with chromaffin cells (sympathetic PGLs/PCs).…”
Section: Sdhb Knockdown Is Associated With Increased Mir-210 Levelssupporting
confidence: 91%
“…Mechanisms other than germline SDHx mutations, including mutations in as yet unidentified susceptibility gene(s) affecting SDH complex assembly/function, abnormal functional interactions with mitochondrial proteins, and/or epigenetic alterations, could be responsible for loss of protein expression (57,58). Another plausible explanation is that HIF1a accumulation due to impaired hydroxylation in hypoxic areas (59) might have resulted in downregulated SDHB expression either in an auto-regulatory loop (60) or through a putative signaling axis involving HIF1a/microRNA-210/iron-sulfur cluster scaffold protein (ISCU) (61).…”
Section: Discussionmentioning
confidence: 99%